2019
DOI: 10.3390/molecules24010186
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Approach to the Dynamics and Structure of Protein Amyloids

Abstract: Amyloid diseases, including neurodegenerative diseases such as Alzheimer’s and Parkinson’s, are linked to a poorly understood progression of protein misfolding and aggregation events that culminate in tissue-selective deposition and human pathology. Elucidation of the mechanistic details of protein aggregation and the structural features of the aggregates is critical for a comprehensive understanding of the mechanisms of protein oligomerization and fibrillization. Vibrational spectroscopies, such as Fourier tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 179 publications
(222 reference statements)
3
42
0
Order By: Relevance
“…In addition to the main band near 1630 cm –1 , a smaller band at higher wavenumbers is also observed near 1685 cm –1 . Such a double-band feature in the amide I region of IR spectra for protein oligomers and early aggregates has been repeatedly reported and is consistent with the accepted IR signature for antiparallel β-sheets, 29 , 49 51 which is in line with theoretical considerations. 52 54 Furthermore, a combined experimental–computational study of mixtures of unlabeled and 13 C-labeled peptides concluded that each peptide molecule contributes at least two adjacent β-strands to the β-sheets of the oligomers, which is consistent with an antiparallel β-hairpin structure.…”
Section: Results and Discussionsupporting
confidence: 89%
“…In addition to the main band near 1630 cm –1 , a smaller band at higher wavenumbers is also observed near 1685 cm –1 . Such a double-band feature in the amide I region of IR spectra for protein oligomers and early aggregates has been repeatedly reported and is consistent with the accepted IR signature for antiparallel β-sheets, 29 , 49 51 which is in line with theoretical considerations. 52 54 Furthermore, a combined experimental–computational study of mixtures of unlabeled and 13 C-labeled peptides concluded that each peptide molecule contributes at least two adjacent β-strands to the β-sheets of the oligomers, which is consistent with an antiparallel β-hairpin structure.…”
Section: Results and Discussionsupporting
confidence: 89%
“…Because no halogen bond was observed in the crystal, and because Raman spectra of the crystal and the gel state displayed analogous signature, we inferred that the red shift was simply a manifestation of the hydrophobic environment surrounding the iodine atom as a result of self-assembly. 50 , 51 In the amide I region, the signal at 1664 cm –1 in the powder was shifted to 1685 cm –1 in the gel and crystal states, as a result of the extended hydrogen-bonding pattern between amides. 52 , 53 Similarly, the signal at 1250 cm 1 in the amide III region, resembling the β-sheet signature, was clearly visible in the gel and crystal states.…”
Section: Resultsmentioning
confidence: 99%
“…These peaks have shifted to lower energies, which indicates a decrease in the molecular vibration due to a weaker strain on the vibrating molecules. Such as been specified above, proteins aggregation induces a shift to a lower frequency in the secondary structure [46,47]. This peak shift can also be supported by arguing that out of plane bending in combination with other molecular vibrations leave molecules more susceptible to be twisted by the magnetic field.…”
Section: Discussionmentioning
confidence: 58%